Penggunaan Media Padlet dalam Membangun Minat Belajar Siswa pada Mapel Pendidikan Agama Islam di SMA Negeri 1 Luhak Nan Duo - Satrianis, Satrianis; Kanus, Oktari (Lembaga Yasin AlSys, 2025)
The development of information technology has had a significant impact on the learning process, including in the subject of Islamic Religious Education (PAI). However, low student interest in learning at SMA Negeri 1 Luhak Nan Duo remains a major challenge in optimizing PAI instruction. This study aims to analyze the implementation of Padlet media in efforts to increase student interest in PAI. The method used is qualitative research with a descriptive approach. Data were collected through interviews, observation, and documentation involving PAI teachers and tenth-grade students in Phase E4. The results show that the use of Padlet media positively influences students' learning interest, as evidenced by increased active participation, attention, and engagement during lessons. Students showed greater enthusiasm and felt more motivated to follow the lessons when Padlet was used as a learning medium. The conclusion of this study is that the use of Padlet media is effective in increasing students’ interest in learning PAI. The implications of this study suggest that integrating technology into learning not only enriches teaching methods but also helps create a more interactive and enjoyable learning environment. Therefore, digital media such as Padlet can be recommended as an alternative in the learning process at schools, especially in supporting students’ interest in learning.